Perceptions towards accounting career among Malaysian undergraduates / Jamaliah Said ... [et al.] - Said, Jamaliah; K. Ghani, Erlane; Hashim, Afizah; Mohd Nasir, Noraini (Faculty of Accountancy, 2004)
In the late 20th Century and the early part of the 21st Century, the accounting profession has suffered some setback in its image. The recent scandal involving Enron and Arthur Andersen may have an adverse impact on the career choice of accounting students. On the other hand Malaysia needs more accountants to assist the country to achieve developed nation status by year 2020. Therefore, this study is an attempt to determine whether accounting students still prefer to become accountants and to compare the perception of accounting as a career between first semester and final semester accounting undergraduates in Malaysia. One thousand questionnaires were distributed to these two groups of students in all the universities registered with the Ministry of Education. The valid response rate was 52.7%. The results of this study show a significance difference in career choices between first semester and final semester students. Of the first semester student respondents, 30.3% prefer to be public accountants, whereas only 25.8% of the final semester respondents choose to be public accountants. However, both groups agree that starting salary is an important criterion for choosing accounting as a career and that their university has provided them with adequate knowledge to enable them to join the accounting profession.